Strategies for an effective implementation of collaborative work on Secondary-Education Teachers of an Integration Program (Revista INTEREDU11, 2023)
This research has been carried out in a public multipurpose school for secondary education, in Osorno, where the need for research upon collaborative teaching work and co-teaching has been identified. The objective of this study is to improve the collaborative work and co-teaching processes, through the acknowledgement of a set of specific actions or strategies on such teachers. This study has been structured under an action-research approach, and it has been developed in three phases: diagnostic, design and implementation of the work plan, and a final assessment, or closure phase. Data collection has been carried out in two different moments, being the diagnostic phase carried out through a quantitative approach, and the closure assessment phase through a mixed approach. The initial sample was composed by eight teachers. Four of them from differential education; three from regular education; and one from a technical school. Thanks to the implementation of the work plan, it has been possible to identify significant progress and positive feedback from the participants, regarding a greater knowledge on the standards that guide collaborative work, and the incorporation of practices or strategies that improve quality.
Keywords: inclusive educatión; school integration; action research; Collaborative work